p53 gene analysis in childhood B non - Hodgkin’s lymphoma - Klumb, Claudete Esteves Nogueira Pinto (2001)
CONTEXT: Mutations or deletions in the tumor- suppressor gene p53 are among the commonest genetic changes found in human neoplasms including breast, lung and bowel cancers. In hematological malignancies, p53 is most often mutated in Burkitt’s lymphoma, with p53 mutations present in 30 to 40% of tumors amples and in 70% of cell lines. OBJECTIVE: To analyze the p53 gene alterations in child patients with B non-Hodgkin’s lymphoma. DESIGN: Descriptive study. SETTING: Tertiary oncology care center. PARTICIPANTS: The study investigated 12 patients with childhood B non-Hodgkin’s lymphoma (Burkitt’s lymphoma).Screening for p53 mutations was done by polymerase chain reaction - single strand conformation alpolymorphism (PCR-SSCP) analysis of exon 5 to 8/9 of the gene. RESULTS: Abnormal polymerase chain reaction - single strand conformational polymorphism migration pattern was observed in 4 patients (33.3%), one on exon 6 and three on exon 7. Positive cases included 2 patients who died from disease. CONCLUSION: These preliminary results suggest that p53 mutations are quite frequent in children with Burkitt’s lymphoma and may play a role in lymphoma genesis or disease progression.